Detection and Tracking of Pedestrian in Various Light Condition - Chate, Manisha; Narayan Mohanty, Mihir; Gohokar, Vinaya (International Journal of Psychosocial Rehabilitation, 2020)
Surveillance systems are to be effective in the current scenario, for which development is the challenging task for researchers. The major challenge is pedestrian detection in various conditions of light. This can well assist the advanced driver system. In this paper, an approach is considered for pedestrian detection and tracking. It can avoid the collision among vehicles and pedestrians as well. The different conditions of light are considered to be day, night, and fog. Therefore, a dataset is developed also. The results are compared with the standard multispectral dataset KAIST. Experimental results show the performance as high as possible.